Prince Myshkin’s Brides in F.M. Dostoevsky’s Novel The Idiot - Victoria M. Fedorova (Russian Academy of Sciences. A.M. Gorky Institute of World Literature, 2019)
The article examines the figures of the two brides in F.M. Dostoevsky’sAbstract: The article examines the figures of the two brides in F.M. Dostoevsky’snovel The Idiot. It considers the word “bride” and its meaning in the novel and traces the paths of the female protagonists – Aglaya Ivanovna and Nastasya Filippovna –the paths of the female protagonists – Aglaya Ivanovna and Nastasya Filippovna –towards this status. It tries to explain why no one of Prince Myskin’s brides becamehis wife and suggests a hypothesis why no one of them could be his spouse. NastasyaFilippovna’s tragedy was that the Prince was not Christ, while Aglaya could notunderstand how to love without separating themselves from all.